Interview with representatives of the Family Asociation Rondilla and "La Unión" of Pajarillos (Ciudades, 2018)
The technical writing of "Estudio para la remodelación de los barrios de Pajarillos y Rondilla de Valladolid" was made for the University Institute for urban Research of the University of Valladolid (IUU) collaborating with Inzamac-TEcopy. Nevertheless, the ideas and opinions of the actors involved and, specially, of the main neighbourhood asociations on both have been just as important on the ellaboration of this document and are vital to understand the process.Therefore, due to the award obtained on this work on the European competition promoted in Gubbio by the national Association of historic-artistic centres in Italy, the IUU has wanted to give way on the pages of its magazine for the voice of those other makers of this small achievement and María Castrillo, member of the writing team, has interviewed to neighbourhood representative: Ángel Bayón, member of the Asociación familiar Rondilla, and José Miguel Gutiérrez, historic leader of the Asociación de vecinos “La Unión” of Pajarillos
Keywords: interview; neighbourhood associations; Gubbio 2003